Rkuhp: Judicial Pardon Concept In Corruption Crime - Lukman Nul Hakim; Nursita Fierdiana Dwi Andariesta; Regina Kartika Sari; Tsania Aziziyah (IHSA Institute, 2022)
In Judicial Pardon/Rechterlijk Pardon is a new concept of punishment in Indonesia which means that a criminal perpetrator is proven guilty, but not sentenced by a judge in a court of law. The draft of the criminal law draft in 2016 resulted in a renewal of the decision referred to as Rechterlijk Pardon (Judge Pardon) against criminal offenders who are legally proven guilty of committing offenses / criminal acts, for example in the case of corruption. This research seeks to reveal the concept of judicial pardon in criminal law reform in Indonesia and to find out that is it possible for judicial pardon to be used in instances of corruption?. This research is a normative legal research by applying two approaches, namely statute approach and conceptual approach. In conclusion, with the criminal law reform, the RKUHP will include and regulate Special Criminal Acts into a single unit. Especially the crime of corruption contained in a separate chapter that the author associates with the principle of judicial pardon. With the Supreme Court decision of the Republic of Indonesia number 42K/Kr / 1965 dated January 8, 1966, the punishment system in corruption crimes can be sentenced to criminal decisions with leniency and loose decisions. So that Judicial Pardon cannot be applied in corruption crimes.